The formation of onion-like carbon-encapsulated cobalt carbide core/shell nanoparticles by the laser ablation of metallic cobalt in acetone - Zhang, Hemin; Liang, Changhao; Liu, Jun; Tian, Zhenfei; Shao, Guosheng (Carbon (New York), 2013)
We developed a new approach to obtain onion-like carbon-encapsulated cobalt carbide (Co3C) core/shell nanoparticles (NPs) by the laser ablation of cobalt in acetone. The as-synthesized core/shell NPs were then characterized by transmission electron microscopy (TEM), X-ray diffraction, Raman spectroscopy, superconducting quantum interference device magnetometer and fluorescence spectrophotometer. TEM observation reveals that the Co3C core is encapsulated by graphitized carbon layers. The number of carbon layers shows certain relationship with the size of the core Co3C NPs. The as-derived core/shell NPs presents unique superparamagnetic property and excitation wavelength-dependent fluorescence. The formation of the carbide and carbon layer can be explained by the laser-induced catalytic cracking of the carbon-rich precursor, acetone molecules. The supersaturated carbon atoms in carbide core tend to be excluded and automatically grow as carbon layers during the subsequent rapid quenching process.